THE INVOLVEMENT OF ENDOTHELIAL DYSFUNCTION MARKERS IN THE PATHOGENESIS OF CHRONIC GLOMERULONEPHRITIS - T.V. Margieva; T.V. Sergeeva (Вопросы современной педиатрии, 2006)
Chronic glomerulonephritis remains the leading cause of formation of chronic renal insufficiency, which creates the necessity of looking for new ways of the progress impediment. In the last few years considerable interest was aroused in the study of the endothelium state, especially taking into account a wide spectrum of its physiologically important functions. The term «endothelial dysfunction» came into existence, its decisive importance in the pathogenesis of the development and progressing of the atherob sclerotic process, arterial hypertension was proven. Extensive studies are underway to establish the role of the endothelial dysfunction in case of chronic inflammatory diseases, including chronic glomerulonephritis. This article summarizes the modern views on the involvement of endothelial dysfunction markers (nitric oxide, endothelinb1, molecules of vascular cytoadherenceb1, von willebrand factor, inhibitor of plasminogenb1 activator) in the pathogenesis of chronic glomerulonephritis. Key words: endothelial dysfunction, nitric oxide, endothelin, molecule of vascular cytoadherence-1, von willebrand factor, inhibitor of plasminogen-1 activator.